Cost Analysis Terapi Antidiabetik pada In Patient Diabetes Melitus Tipe 2 di RSU Anwar Medika - Jalmav, Marthy Meliana Ariyanti; Yuniati Hoiriyah, Yuniati (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Diabetes is a complex chronic disease that requires ongoing medical care with multifactorial risk reduction strategies beyond glycemic control. This study aims to describe the direct medical costs from the perspective of Anwar Medika General Hospital in type 2 Diabetes Mellitus (DM) patients who use the National Health Insurance (JKN) facility and to see the difference between real costs (total direct medical costs) and INA CBG's costs. The study was retrospective for the past 1 year, namely January-December 2020. The subjects of this study were 54 patients. Mann- Whitney analysis is used to see the suitability of real costs with INA-CBG's tariffs. The results of this study show that the total real cost for JKN type 2 DM patients at Anwar Medika Hospital for the January-December 2020 period is Rp. 269,807,380 and there is a difference between real costs and INA-CBG's costs in class 3 of - 4,190,371 where INA-CBG's costs are -4,190,371. CBG's are less than the real hospital costs. The test results using the Mann-Whitney method show an insignificant difference between real costs and INA-CBG's rates. The result p=0.458 where p>0.05 is said to be insignificant. This could be due to a cross-subsidy between INA CBG’s rate claims of fully unused patients and patients who spend more on treatment costs exceeding INA CBG’s rates.